METHODS FOR TEACHING SPEAKING SKILLS IN MODERN PEDAGOGY - Djumanova Barno, Djumanova Barno (Журнал иностранных языков и лингвистики, 2021)
Speaking is "the process of building and sharing meaning through the use of verbal and non-verbal symbols, in a variety of contexts" (Chaney, 1998, p. 13). Speaking plays a crucial role in second language learning and teaching. Despite its importance, for many years, teaching speaking has been undervalued and English language teachers have gone on teaching speaking just as a repetition of drills or memorization of dialogues. However, today’s world requires that the goal of teaching speaking should improve students’ communicative skills. This paper purposes to explore some innovative teaching methods, techniques and activities used for developing speaking fluency and its effects of pupils oral competency.